Dust evolution in galaxies at z > 7. Issue Volume 15:Issue S341(2019) (November 2019) - Takeuchi, Tsutomu T.; Asano, Ryosuke S.; Nagasaki, Sayaka; Nozawa, Takaya; Tamura, Yoichi; Mawatari, Ken; Inoue, Akio K.
Abstract: Recently huge amount of dust M dust ≃ 10 6−7 M ⊙ in galaxies at z = 7–8 has been discovered by ALMA observations. The suggested timescale of the dust production was a few–several×10 8 yr, while the stellar mass was several × 10 9 M ⊙ . This amount of dust cannot be easily explained only by a supply from supernovae if we consider the dust destruction by reverse shocks. We propose that these values can be consistently explained if we take into account the grain growth in the interstellar medium (ISM). This scenario successfully reproduces the evolution of the dust mass, as well as the SFR, and stellar mass simultaneously. We conclude that even at such an early epoch of the Universe, the dust grain growth in the ISM plays a significant role in galaxies.